Acral Syringotropic Melanoma in situ with Eccrine Duct Hyperplasia - Tachibana, Mitsuhiro; Kitano, Seiya; Mikura, Ayako; Fujimoto, Masakazu; Ohara, Kuniaki; Izumi, Miki; Tsutsumi, Yutaka (Archives of Clinical and Medical Case Reports, 2021)
Acral syringotropic melanoma with eccrine duct hyperplasia (ASMEDH) is rare. We describe ASMEDH arising in the right sole of a Japanese woman aged 80’s. On a 15 x 10 mm-sized, irregular-shaped pigmented macule, the dermoscopy indicated pararrel ridges. The lesion was removed surgically. No nodal swelling was noted. Microscopically, the pigmented melanoma cells were distributed not only in the basal epidermis but also in the cutaneous sweat gland duct. The melanoma cells were positive for HMB45, melan A, S-100 protein, bcl-2, vimentin, CD5 and SOX10, but negative for cytokeratins (CKs) and adipophilin. Ki-67 labeling was around 10%. In the dermis, basal cells immunoreactive for CK 34βE12, CK5/6 and p40 surrounded the intraductally spreading melanoma cells and ductal lumina were frequently located in the center. Invasive growth was absent. The surgical margins were negative. The patient did not receive adjuvant chemotherapy, and she is doing well eight months after surgery. Our final diagnosis was ASMEDH, melanoma in situ, the third case in the world.